Oczekiwania i decyzje gospodarstw domowych oraz przedsiębiorstw a makroekonomiczne konsekwencje polityki gospodarczej - Krawczyk, Marcin (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2016)
The paper describes different approaches in the theory of economics (from Phillips curve through ricardian equivalence theorem to the demand for money) to the expectations of business entities on the future shape of basic macroeconomic aggregates. Inclusion of such expectations in theoretical framework of economics changes described economic processes and leads to change in the conclusions.